2013
DOI: 10.22610/imbr.v5i10.1078
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Capital, Corporate Governance and Firm Performance

Abstract: This paper aims to exam the connection among intellectual capital, corporate governance and firm performance. Firm performance measured by Tobin’s Q is an important indicator. Business function such as R&D, advertising, and human resources, after adjusting for sales, remains important factors. Especially, management team should be aware of using leverage because excessive debt usage leads to poor Tobin’s Q. Investors should be cautious of capital structure when forming their investment portfolios. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…In both cases the coefficient OC also assumes a positive value, although not statistically significant. The results obtained are similar to those of Saleh et al (2009), Bohdanowicz and Urbanek (2013), and Tsai et al (2013).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In both cases the coefficient OC also assumes a positive value, although not statistically significant. The results obtained are similar to those of Saleh et al (2009), Bohdanowicz and Urbanek (2013), and Tsai et al (2013).…”
Section: Resultssupporting
confidence: 91%
“…The relationship between IC and ownership structure except for in emerging countries has been, to the authors' knowledge, little investigated. Among the studies that examine the relationship between IC and ownership structures are Firer and Williams (2005), Saleh, Rahman, and Hassan (2009), Tsai, Yu, and Wen (2013), Kalyta (2013), and more recently Bohdanowicz and Urbanek (2013).…”
Section: Ic Ownership Structure and Firm Performancementioning
confidence: 99%
“…Commonly within the social sciences, intangibles are classified as knowledge resources (Nonaka and von Krogh, 2009; Miller and Choi, 2010; Tsai et al , 2013a); as intellectual capital (Roos et al , 1997; Marr et al , 2004; Schiuma et al , 2008; Celenza and Rossi, 2014); or as intangible assets (Hall, 1992; Lev, 2001; Lopes and Rodrigues, 2007; Ittner, 2008; Lopes, 2010; Tanfous, 2013). Dependent on accounting rules, several studies (Moeller, 2009; Zéghal and Maaloul, 2010; Kianto et al , 2013; Tsai et al , 2013b; Salchi et al , 2014; Shakina and Molodchik, 2014; Tudor et al , 2014; Vallejo-Alonso et al , 2015) have identified and measured the impact of intangibles on value-creation and performance in business. Traditionally, intellectual capital can be split into two main categories: human capital and structural capital (Roos et al , 1997).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…There were some researches on the relationship among managerial ownership or ownership concentration, company performance and ICE (Celenza & Rossi, 2013;Tsai, Yu, & Wen, 2013). Some of these researches concerned the relationship between ICE and managerial ownership (Bohdanowicz & Urbanek, 2013;Saleh, Rahman, & Hassan, 2009), but as Celenza and Rossi (2013) stated, especially the association between intellectual capital and ownership structure was little examined.…”
Section: Ownership and Intellectual Capitalmentioning
confidence: 99%
“…Different variables on intellectual capital are used studies of Tsai et al (2013). They investigated companies listed on the Taiwan stock exchange between 2004 and 2008.…”
Section: Ownership and Intellectual Capitalmentioning
confidence: 99%